1993
DOI: 10.1111/j.1476-5381.1993.tb13647.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo release of dopamine from rat striatum, substantia nigra and prefrontal cortex: differential modulation by baclofen

Abstract: 1 The effect of baclofen, a GABAB receptor agonist, on the release of dopamine from the striatum (ST), substantia nigra (SN) and prefrontal cortex (PFC) of the rat was examined by intracerebral microdialysis. 2 Perfusion of baclofen 50 LM did not affect the striatal release of dopamine. However, dopamine release was markedly reduced in the SN and PFC. 3 3,4-Dihydroxyphenylacetic acid and homovanillic acid output increased in the ST and decreased in the SN and PFC when baclofen was perfused through the microdia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 44 publications
2
25
0
Order By: Relevance
“…2). GABA released from these neurons may inhibit dopamine release by activating GABA B receptors in the medial prefrontal area (Santiago et al, 1993). This suggestion is compatible with the coupling of 5-HT 2A receptors to G q proteins and, accordingly, their excitatory rather than inhibitory effect.…”
supporting
confidence: 73%
“…2). GABA released from these neurons may inhibit dopamine release by activating GABA B receptors in the medial prefrontal area (Santiago et al, 1993). This suggestion is compatible with the coupling of 5-HT 2A receptors to G q proteins and, accordingly, their excitatory rather than inhibitory effect.…”
supporting
confidence: 73%
“…Thus, the lack of effect of intraCPu baclofen is more likely because CPu GABA B receptors are not involved in acute amphetamine-induced behaviors than to the heterogeneity of the striatum. Similarly, GABA B receptors in the mPFC appear not to be involved in the motor stimulatory effects of acute amphetamine although intra-mPFC baclofen decreases nomifensine-induced extracellular dopamine levels in PFC (Santiago et al, 1993). Similarly, selective quinolinic acid-induced lesions of the prelimbic cortex (Cg3), which only destroy intrinsic neurons, did not affect locomotion and rearing responses induced by amphetamine (Tzschentke and Schmidt, 1998).…”
Section: Effects Of Intracerebral Baclofen On Amphetamine-induced Behmentioning
confidence: 99%
“…In support of the regional differences in baclofen's effectiveness, perfusion of baclofen into the SN decreased basal and nomifensine-induced extracellular dopamine levels in the SN and CPu, but infusion into the CPu did not decrease striatal dopamine levels (Westerink et al, 1992;Santiago et al, 1993;Balon et al, 2002). GABA B receptors are expressed by striatonigral, striatopallidal, and glutamatergic afferents as well as by dopamine and GABA neurons in the SN and VTA (Sugita et al, 1992;Charara et al, 2000;Boyes and Bolam, 2003).…”
Section: Effects Of Intracerebral Baclofen On Amphetamine-induced Behmentioning
confidence: 99%
“…The activation of GABAB receptors both at the somatodendritic (Westerink et al, 1996) and at the terminal level (Santiago et al, 1993) has been suggested to result in decreased mesocorticolimbic DA release. Our present results suggest that the action at the nerve terminal level is not strong enough to inhibit the stressinduced increase in DA release in the PFC.…”
Section: Figmentioning
confidence: 99%